Loss of chloroplast‐localized protein phosphatase 2Cs in Arabidopsis thaliana leads to enhancement of plant immunity and resistance to Xanthomonas campestris pv. campestris infection. (2nd November 2017) - Akimoto‐Tomiyama, Chiharu; Tanabe, Shigeru; Kajiwara, Hideyuki; Minami, Eiichi; Ochiai, Hirokazu
Summary: Protein phosphatases (PPs) counteract kinases in reversible phosphorylation events during numerous signal transduction pathways in eukaryotes. PP2Cs, one of the four major classes of the serine/threonine‐specific PP family, are greatly expanded in plants. Thus, PP2Cs are thought to play a specific role in signal transduction pathways. Some rice PP2Cs classified in subgroup K are responsive to infection by the compatible Xanthomonas oryzae pv. oryzae, the causal agent of bacterial blight. In Arabidopsis thaliana, orthologous PP2C genes ( AtPP2C62 and AtPP2C26 ) classified to subgroup K are also responsive to Xanthomonas campestris pv. campestris ( Xcc, causal agent of black rot) infection. To elucidate the function of these subgroup K PP2Cs, atpp2c62 ‐ and atpp2c26 ‐deficient A. thaliana mutants were characterized. A double mutant plant which was inoculated with a compatible Xcc showed reduced lesion development, as well as the suppression of bacterial multiplication. AtPP2C62 and AtPP2C26 localized to the chloroplast. Furthermore, the photosynthesis‐related protein, chaperonin‐60, was indicated as the potential candidate for the dephosphorylated substrate catalysed by AtPP2C62 and AtPP2C26 using two‐dimensional isoelectric focusing sodium dodecylsulfate‐polyacrylamide gel electrophoresis (2D‐IDF‐SDS‐PAGE). Taken together, AtPP2C62 and AtPP2C26 are suggested to be involved in both photosynthesis and suppression of the plant immune system. These results imply the occurrence of crosstalk between photosynthesis and the plant defence system to control productivity under pathogen infection.